Madame Tussaud and the history of waxworks - Pilbeam, Pamela M. (London ; New York : Hambledon and London, 2003)
Chapter 1: The Origins of Wax Modelling Chapter 2: The Wax Salon Chapter 3: Revolutionary Paris Chapter 4: The Travelling Wax Exhibition Chapter 5: The Baker Street Bazaar Chapter 6: Wax Rivals Chapter 7: From the Great Exhibition to the First World War Chapter 8: Waxworks in the Age of Film Chapter 9: The Appeal of Waxworks
Includes bibliographical references (p. [265]-277) and index.
boek
Keywords: Tussaud, Marie